2013
DOI: 10.1128/jvi.01204-13
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Prophylactic Efficacy of Oral Maraviroc in Macaques despite High Drug Concentrations in Rectal Tissues

Abstract: Maraviroc (MVC) is a potent CCR5 coreceptor antagonist that is in clinical testing for daily oral pre-exposure prophylaxis (PrEP) for HIV prevention. We used a macaque model consisting of weekly SHIV 162p3 exposures to evaluate the efficacy of oral MVC in preventing rectal SHIV transmission. MVC dosing was informed by the pharmacokinetic profile seen in blood and rectal tissues and consisted of a human-equivalent dose given 24 h before virus exposure, followed by a booster postexposure dose. In rectal secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 45 publications
(67 reference statements)
3
54
1
Order By: Relevance
“…Recent work by Massud et al suggested that rectal delivery of maraviroc gels lacks efficacy in a macaque SHIV challenge model and may be complicated by effects of rectally applied maraviroc on populations of CD3 ϩ /CCR5 ϩ cells (40). It remains to be seen if maraviroc can serve as an effective microbicide in humans, either intravaginally or rectally.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Massud et al suggested that rectal delivery of maraviroc gels lacks efficacy in a macaque SHIV challenge model and may be complicated by effects of rectally applied maraviroc on populations of CD3 ϩ /CCR5 ϩ cells (40). It remains to be seen if maraviroc can serve as an effective microbicide in humans, either intravaginally or rectally.…”
Section: Discussionmentioning
confidence: 99%
“…The observed median steady-state MVC level of 20 g g Ϫ1 (40 M) in vaginal tissues was 3,000 times higher than the highest 90% inhibitory concentration, suggesting possible favorable pharmacodynamic outcomes. However, in a macaque model involving rectal exposure, MVC concentrations in rectal secretions that were predicted to provide prophylactic efficacy (C max , 10.2 g ml Ϫ1 ) failed to protect macaques from SHIV infection (26), suggesting that prophylactic efficacy cannot be easily predicted based on MVC tissue levels. Additional efficacy studies in macaques with MVC alone and in combination with other ARVs are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of TDF, TFV, FTC, and MVC in vaginal fluid, cervicovaginal lavage (CVL) fluid, vaginal tissue homogenate, and plasma samples were measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS) using published methods (15,18,25,26). The lower limits of quantitation (LLOQs) for these analytes in the aforementioned sample matrices are presented in Table 2.…”
Section: Materials Tenofovir Disoproxil Fumarate (Tdf) and Emtricitamentioning
confidence: 99%
“…Preliminary studies with macaques have demonstrated that oral administration of MVC (44 mg/kg) alone is insufficient to prevent HIV infection despite high drug concentration in rectal tissues 24 h prior to inoculation [55]. Nonetheless, MVC has been pushed to human trials in the NEXT-PrEP (Novel Exploration of Therapeutics for PreExposure Prophylaxis) study although no data on the outcome of the study are available at the time of this writing [56].…”
Section: First-generation Ccr5 Antagonistsmentioning
confidence: 99%